2018
DOI: 10.1101/483131
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Immunological Diversity with Similarity

Abstract: A diverse immune repertoire is considered a hallmark of good health, but measuring diversity requires a framework that incorporates not only sequences’ relative frequencies but also their functional similarity to each other. Using experimentally measured dissociation constants from over 1,300 antibody-antigen and T-cell receptor (TCR)-peptide pairs, we developed a framework for functional immunological diversity based on binding and applied it to nearly 400 high-throughput antibody and TCR repertoires to revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 63 publications
1
20
0
Order By: Relevance
“…As proof of principle, we fit descriptor models on 31 before-and-after IgG+ repertoires (including three replicates) from 14 healthy human volunteers who were administered a seasonal trivalent influenza vaccine (Vollmers et al, 2013). We had previously shown that vaccination leads to prominent changes in both repertoires’ raw and functional diversity (Arora et al, 2018), but withheld diversity measurements from the present study in order to test the discriminatory power of the models in the absence of that additional information. Using stratified 3-fold cross-validation, we found that descriptor models distinguished between pre- and post-vaccination pairs with median AUC of 0.97 ( p =4×10 -3 ; Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As proof of principle, we fit descriptor models on 31 before-and-after IgG+ repertoires (including three replicates) from 14 healthy human volunteers who were administered a seasonal trivalent influenza vaccine (Vollmers et al, 2013). We had previously shown that vaccination leads to prominent changes in both repertoires’ raw and functional diversity (Arora et al, 2018), but withheld diversity measurements from the present study in order to test the discriminatory power of the models in the absence of that additional information. Using stratified 3-fold cross-validation, we found that descriptor models distinguished between pre- and post-vaccination pairs with median AUC of 0.97 ( p =4×10 -3 ; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We note that vaccination, like many immunological perturbations, results in systems-as well as sequence-level changes; for example, changes in immunological/repertoire diversity (Jiang et al, 2013; Vollmers et al, 2013). We pre viously showed that the combination of raw and functional diversity, measured with various frequency weightings, can discriminate between pre- and post-vaccination sample pairs with high accuracy, likely in part by detecting clonal expansion with selection (Arora et al, 2018). However, changes in diversity, while potentially useful as part of a screening test, are not sufficiently specific to serve as a general diagnostic modality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently we introduced a computational method for investigating repertoire-wide antigen binding, using thousands of K d measurements for amino-acid substitutions to establish and validate a mean-behavior model for structural similarity among all pairs of antibodies in a repertoire directly from repertoire sequence. 9 That work revealed that repertoires are organized into loose overlapping classes of antibodies with similar predicted functionality, and suggested that these classes may be widely shared among repertoires from across individuals, notwithstanding low sequence overlap between repertoires.…”
mentioning
confidence: 99%